Putting on partisan glasses: Political identity, quality of life, and oil and gas production in Colorado. (June 2019) - Malin, Stephanie A.; Mayer, Adam; Crooks, James L.; McKenzie, Lisa; Peel, Jennifer L.; Adgate, John L.
Abstract: Unconventional oil and gas technologies—such as hydraulic fracturing—have drastically increased the volume of oil and gas produced in the U.S., while simultaneously bringing drilling closer to residential areas. We examine quality of life impacts of unconventional oil and gas production, arguing that how people perceive its local effects is rooted in their political identities. Using survey data from three northern Colorado communities, we employ counterfactual mediation methods to understand relationships between political identity, perceived socio-environmental and community changes from oil and gas development, and self-reported quality of life. We find significant differences in how people perceive local development based upon political identity, whereby Tea Party supporters see little negative impact, and in turn are likely to believe that local development improves their quality of life. At the other extreme, Democrats perceive more negative community changes from oil and gas development and are more apt to believe that it reduces their quality of life. Republicans who do not support the Tea Party and political independents hold more mixed views. Overall, our analysis suggests that people's perceptions of local energy development and how it matters for their quality of life is, to some degree, a function of their political identities. Highlights: Surveyed three communities in Northern Colorado with varying levels of oil and gas production. Modeled political identity, perceived impacts of oil & gas production, & self-reported quality of life. Findings suggest partisan motivated cognition regarding unconventional oil and gas (UOG) production. Different political identities engender divergent perspectives on UOG production's community effects. And divergent perceptions of how perceived community changes impact quality of life.